Foreign direct investment, institutional development, financial development and economic growth - Rajab bouzayani; Zouheir Abida (European Journal of Volunteering and Community-Based Projects, 2021)
The aim of this paper is to focus on relationship between FDI, financial development, institutional development and economic growth in North African countries from 1995 to 2017. Using the system Generalized Method of Moments (GMM) in a panel data analysis, we justify the positive effect of FDI, institutional development and financial development on the economic growth in North African countries. We also noted the important complement between FDI, institutional development and financial